Effects of Temperature and Amount of Ion Exchange Resin on Ion Exchange Reaction Rate - LOKHANDE, R.S.; A. PARAB, SANGEETA (Asian Journal of Chemistry, 2010)
The kinetics of ion exchange reaction has been studied by the application of 131I as a tracer isotopes. The exchange rate of ion exchange resin Duolite A-116 have been determined. Kinetics of ion exchange at different temperature ranging from 25 to 45ºC and particularly at low concentration of eletrolyte (KI) ranging from 0.0025 to 0.04 M and for different amount of ion exchange resin ranging from 0.25 to 2.0 g has been carried out.